MENGATASI ISU SARA DAN MENINGKATKAN KOHESI SOSIAL MELALUI TEORI -TEORI PENDIDIKAN MULTIKULTURAL - Siti Zalfa Pratiwi; Dwi Putri Amelia; Nurul Qomariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesia is a multicultural country characterized by a rich diversity of ethnicities, religions, races, and intergroup relations, which serve as both a valuable asset and a challenge in maintaining unity. In recent decades, various conflicts rooted in ethnic, religious, racial, and intergroup (SARA) issues have demonstrated that social cohesion remains vulnerable due to a lack of cross-cultural understanding. This study aims to examine the role of multicultural education in addressing SARA issues and strengthening social cohesion through a literature review approach. The study explores relevant theories of multicultural education and previous findings related to its implementation in the context of Indonesian education. The results indicate that multicultural education holds significant potential in shaping students into tolerant, inclusive individuals who respect diversity. It can also contribute to fostering a harmonious social environment by enhancing mutual understanding and intergroup solidarity. Nevertheless, the implementation of multicultural education faces several challenges, ranging from cultural resistance to limitations in policies and teacher training. This study recommends strengthening policies and educational practices that emphasize multicultural values as a strategic effort to build social cohesion in a pluralistic society.